A silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage properties and a preparation method thereof
By introducing NaNbO3 and (Sr0.7Bi0.2)TiO3 into silver niobate-based ceramic materials, the long-range order of ferroelectricity has been broken, the energy storage density and efficiency of silver niobate-based ceramic materials have been improved, and the existing silver niobate has been solved. The problems of low energy storage density and efficiency of base ceramic materials have achieved high energy storage characteristics.
Patent Information
- Application Number
- CN202311269019.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing silver niobate-based ceramic materials have low energy storage density and energy storage efficiency due to ferrous electrical properties, and it is difficult to induce disordered local structures and polar nanomicro regions, resulting in antiferroelectric hysteresis loops. They are all square and straight, making it difficult to achieve a coordinated improvement in energy storage density and energy storage efficiency.
By introducing antiferroelectric component NaNbO3 and relaxation component (Sr0.7Bi0.2)TiO3, a silver niobate-based relaxation ternary solid-solution ceramic material was designed to increase the lattice disorder of the material. and configuration entropy breaks the long-range order of ferroelectricity, realizes narrow inclined electrical hysteresis loops, and improves breakdown field strength and energy storage density.
It significantly improves the breakdown electric field strength, energy storage density and energy storage efficiency of silver niobate-based ceramic materials, realizes the characteristics of narrow oblique electrical hysteresis loops, achieves high saturation polarization and low residual polarization, and is suitable for pulse power capacitors.
Smart Images

Figure CN117285354B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics and a preparation method thereof, and belongs to the field of functional materials. Background Art
[0002] Dielectric ceramic capacitors have excellent power density and ultra-fast charge and discharge rates, and have broad application prospects in the field of energy storage. Currently, commercial high-energy storage ceramic dielectric materials are mainly lead-containing antiferroelectric compounds, but lead-based materials can cause great harm to the ecological environment and human health, so the development of lead-free dielectric materials is an urgent problem to be solved. Silver niobate has a large polarization strength (40μC / cm 2 ) is a popular candidate material for high energy storage applications, but due to its ferroelectricity, the residual polarization strength (4μC / cm 2 ) and the forward transition electric field is low, resulting in low energy storage density and energy storage efficiency.
[0003] In recent years, a lot of work has been done to study the means of improving the energy storage density and efficiency of silver niobate-based ceramics. The main methods are: by doping ions with an ionic radius smaller than silver ions at the A position of the perovskite structure to enhance the stability of the antiferroelectric phase (reference: Energy Storage Mater., 2021, 34: 417-426); doping ions with a polarizability lower than niobium ions at the B position to reduce the residual polarization intensity (reference: Nat. Commun., 2020, 11(1): 4824); doping small radius ions and low polarizability ions at the A and B positions respectively to achieve improved antiferroelectric phase stability and reduced residual polarization intensity (reference: Ceram. Int., 2023, 49(11): 18143-18152). However, current silver niobate-based energy storage ceramics are difficult to induce disordered local structures and polar nano-regions. Therefore, the antiferroelectric hysteresis loops obtained are all square and straight with large hysteresis, making it difficult to achieve a synergistic improvement in energy storage density and efficiency. Summary of the invention
[0004] Based on the above background, the present invention provides a silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics and a preparation method thereof. The novel lead-free dielectric ceramic material of the present invention has excellent energy storage characteristics. By introducing the antiferroelectric component NaNbO3 and the relaxor component (Sr 0.7 Bi 0.2 )TiO3, and a ternary solid solution silver niobate-based ceramic material with greatly improved breakdown field strength and energy storage density is obtained, which has application prospects in pulse power capacitors.
[0005] In the first aspect, the present invention provides a silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics. The chemical composition of the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics is: (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, where 0≤x≤0.25.
[0006] The present invention designs silver niobate-based ceramic materials with complex material composition through multi-system solid solution, increases the material lattice disorder, increases the atomic configuration entropy, breaks the ferroelectric long-range order, and obtains silver niobate-based relaxor ceramics with narrow oblique hysteresis loops. It also combines the advantages of various solid solution systems, thereby achieving a synergistic improvement in energy storage density and energy storage efficiency, and has the characteristics of strong breakdown field and high energy storage density.
[0007] Preferably, 0.18≤x≤0.25.
[0008] Preferably, the breakdown electric field of the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics is 444-489 kV / cm; the recoverable energy storage density is 5.55-6.69 J / cm 3 ; The energy storage efficiency is 53.7~76.9%.
[0009] In a second aspect, the present invention provides a method for preparing a silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage properties. The preparation method comprises:
[0010] (1) According to the stoichiometric ratio (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, weighing silver oxide powder, niobium pentoxide powder, titanium dioxide powder, sodium carbonate powder, bismuth oxide powder and strontium titanate powder as raw material powders, mixing them, calcining and fine grinding them to obtain synthetic powder;
[0011] (2) mixing the obtained synthetic powder and a binder, and then granulating, aging, sieving and molding to obtain a ceramic green body;
[0012] (3) The obtained ceramic green body is subjected to plastic disassembly and sintering to obtain a silver niobate-based relaxation-type ternary solid solution ceramic material with high energy storage properties.
[0013] Preferably, in step (1), the mixing method is ball milling; preferably, anhydrous ethanol is used as the dispersion medium, the ball milling speed is 230 to 250 rpm, and the ball milling time is 4 to 6 hours; more preferably, the ball milling medium is zirconia balls and / or zirconia columns.
[0014] Preferably, in step (1), the calcination atmosphere is an oxygen atmosphere, the calcination temperature is 850-870° C., and the calcination time is 2-4 hours.
[0015] Preferably, in step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 5 to 7 wt%; the amount of the binder added is 6 to 7 wt% of the mass of the synthetic powder; and the sieve has a mesh size of 20 to 80.
[0016] Preferably, in step (3), the temperature of the plastic removal is 700-800° C., and the time is 2-3 hours.
[0017] Preferably, in step (3), the sintering temperature is 980°C to 1060°C, the time is 2 to 3 hours, and the sintering heating rate is not higher than 2°C / min. Preferably, the sintering heating rate is 1 to 2°C / min. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments with reference to the following accompanying drawings.
[0019] Figure 1 X-ray diffraction patterns of Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention;
[0020] Figure 2 This is a surface microscopic morphology diagram of Example 1 of the present invention;
[0021] Figure 3 This is a surface microscopic morphology diagram of Example 2 of the present invention;
[0022] Figure 4 This is a surface microscopic morphology diagram of Example 3 of the present invention;
[0023] Figure 5 This is a surface microscopic morphology diagram of Comparative Example 1 of the present invention;
[0024] Figure 6 This is a surface microscopic morphology image of Comparative Example 2 of the present invention;
[0025] Figure 7 is the change of the dielectric constant of Example 2 of the present invention with temperature;
[0026] Figure 8 is the change of the dielectric constant of Comparative Example 3 of the present invention with temperature;
[0027] Fig. 9 is a unipolar hysteresis loop diagram of Example 1 of the present invention;
[0028] Fig.10 is a unipolar hysteresis loop diagram of Example 2 of the present invention;
[0029] Fig.11 is a unipolar hysteresis loop diagram of Example 3 of the present invention;
[0030] Fig.12 is a unipolar hysteresis loop diagram of Example 4 of the present invention;
[0031] Fig.13 is a unipolar hysteresis loop diagram of comparative example 1 of the present invention;
[0032] Fig.14 is a unipolar hysteresis loop diagram of Comparative Example 2 of the present invention;
[0033] Fig.15 is a unipolar hysteresis loop diagram of Comparative Example 3 of the present invention;
[0034] Fig.16 It is a curve showing the change of energy storage density and energy storage efficiency of the silver niobate-based relaxation type ternary solid solution ceramic material with x. DETAILED DESCRIPTION
[0035] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0036] The chemical composition of the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics (also referred to as "silver niobate-based relaxor-type energy storage ceramic material" or "silver niobate-based relaxor-type energy storage ceramic material for energy storage") of the present invention is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, wherein x = 0 to 0.25. When x is higher than 0.25, the saturation polarization intensity is reduced and the energy storage density is reduced.
[0037] The high energy storage property silver niobate-based relaxor-type ternary solid solution ceramic material of the present invention increases the solid solubility of silver niobate and the breakdown field strength by introducing NaNbO3, and at the same time introduces the relaxation component (Sr 0.7 Bi 0.2 )TiO3 to induce disordered local structure and polar nano-micro-regions, reduce the residual polarization strength and increase the breakdown field strength, thereby improving the energy storage density and efficiency. In other words, the present invention increases the solid solubility of AgNbO3 by introducing NaNbO3, and increases the solubility of AgNbO3 by introducing the relaxation component (Sr 0.7 Bi 0.2 )TiO3, further increasing the configuration entropy of the material system, inducing the relaxation characteristics of the material system, and obtaining excellent energy storage performance. This provides a new idea for the design of new lead-free energy storage material systems.
[0038] NaNbO3 has antiferroelectricity, and its hysteresis loop is straight and has no relaxation characteristics. Introducing only the antiferroelectric component NaNbO3 cannot change the ferroelectric properties of the material system. The hysteresis is still large and the energy storage efficiency is low. (Sr 0.7 Bi 0.2 )TiO3 has relaxation characteristics, and only the relaxation component (Sr 0.7 Bi 0.2 )TiO3 (Sr 0.7 Bi 0.2 )TiO3 cannot form a solid solution with AgNbO3 in large proportions.
[0039] Preferably, 0.18≤x≤0.25. Within this composition range, a narrow hysteresis loop phenomenon can be observed, and a relatively higher breakdown electric field strength, effective energy storage density, and energy storage efficiency can be obtained.
[0040] The silver niobate-based relaxor energy storage ceramic material of the present invention can be prepared by a solid phase reaction method in an oxygen atmosphere. For example, it may include steps such as batching, mixing, briquetting, synthesis, crushing, fine grinding, molding, plastic removal, and sintering. The following is an exemplary description of the preparation method of the silver niobate-based relaxor energy storage ceramic material.
[0041] Step 1: Synthesize by solid phase method. According to the chemical formula, the stoichiometric ratio is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, silver oxide powder, niobium pentoxide powder, titanium dioxide powder, sodium carbonate powder, bismuth oxide powder and strontium titanate powder are weighed as raw material powders and mixed, and synthetic powder is obtained by calcining and fine grinding.
[0042] The purity of the raw material powder is greater than 99%. As an example, silver oxide powder, niobium oxide powder, titanium dioxide powder, sodium carbonate powder, bismuth oxide powder and strontium titanate powder with a purity greater than 99% are selected as raw materials and weighed according to the molar ratio of Ag:Na:Nb:Sr:Bi:Ti=(0.7-0.7x):(0.3-0.3x):(1-x):0.7x:0.2x:x.
[0043] The raw material powders can be uniformly mixed by ball milling. Ball milling parameters include: using anhydrous ethanol as a dispersion medium, a ball milling speed of 230 to 250 rpm, and a ball milling time of 4 to 6 hours. The ball milling medium can be a zirconia ball and / or a zirconia column. For example, zirconia balls with a diameter of 6 mm and a diameter of 10 mm are used as ball milling media. The mass ratio of zirconia balls with a diameter of 6 mm and a diameter of 10 mm can be 3:2. The mass ratio of raw material powder, ball milling medium and anhydrous ethanol during ball milling can be changed as needed. For example, the mass ratio of raw material powder: ball milling medium: anhydrous ethanol can be 1:4.5:1.8. The ball milling (mixing) time can be 4 hours. Drying and sieving can be performed after ball milling. The sieved powder is pressed into blocks at a pressure of 1 to 4 MPa, such as 3 MPa.
[0044] The calcination temperature (synthesis temperature) can be 850-870°C. As an example, a large block of powder to be synthesized is placed in a closed container (e.g., a closed alumina crucible) for synthesis, thereby reducing the volatilization of the Na component and the Bi component and the slag contamination. For example, calcination is performed in a muffle furnace with an oxygen atmosphere. Preferably, the temperature is increased to the synthesis temperature at a heating rate of not more than 2°C / min so that the synthesis reaction occurs fully. The atmosphere of the closed calcination is an oxygen atmosphere. As an example, the calcination temperature is 870°C and the calcination time is 4h.
[0045] After calcination, the furnace may be cooled to room temperature. The synthesized ceramic powder may be crushed and sieved (for example, 20 to 80 meshes), thereby improving the subsequent process efficiency and saving preparation time.
[0046] Step 2: molding the obtained synthetic powder into a ceramic green body (also referred to as a ceramic green body). For example, the synthetic powder is finely ground, granulated, aged and molded into a ceramic green body.
[0047] The synthetic powder can be finely ground before molding. The fine grinding method can be wet ball milling. The ball milling medium can be zirconia balls and / or zirconia columns. For example, the ball milling medium is zirconia columns and zirconia balls. Zirconia balls with diameters of 1 mm, 6 mm, and 10 mm can be used. The mass ratio of zirconia columns, zirconia balls with a diameter of 6 mm, and zirconia balls with a diameter of 10 mm is 1-1.5:1-1.5:1-1.5. The dispersion medium can be anhydrous ethanol. The mass ratio of synthetic powder, ball milling medium, and anhydrous ethanol during ball milling can be changed as needed. For example, the mass ratio of synthetic powder: ball milling medium: anhydrous ethanol can be 1:4.5:1.8. The ball milling speed can be 400-500 rpm. The ball milling time can be 4-6 hours. It can be dried after fine grinding.
[0048] Add a binder for granulation. The binder used for granulation can be a polyvinyl alcohol (PVA) aqueous solution with a concentration of 5 to 7 wt%. As an example, the concentration of the polyvinyl alcohol aqueous solution is 7 wt%. The amount of binder added can be 6 to 7 wt% of the weight of the ceramic powder, for example, 6%. After granulation, it can be aged for a period of time. The aging time can be 24 hours. After aging, it is pressed into shape. A green body of the desired size can be obtained by dry pressing. The pressing pressure can be 1 to 3 MPa, for example, 1.5 MPa.
[0049] The ceramic green body is subjected to molding and sintering to obtain the silver niobate-based ceramic material.
[0050] The temperature of the plastic discharge is 700-800°C, and the time is 2-3 hours. The atmosphere of the plastic discharge is an oxygen atmosphere. In some embodiments, the plastic discharge conditions can be: heating to 700°C at a heating rate of no more than 2°C / min in an oxygen atmosphere, keeping the temperature for 2 hours, and cooling to room temperature with the furnace.
[0051] The ceramic blank after plastic removal is sintered in an oxygen atmosphere at a sintering temperature of 980-1060° C. and a holding time of 2 hours. Preferably, the heating rate of the sintering is 2° C. / min.
[0052] According to the preparation process of the present invention, by controlling the sintering temperature within 980-1060° C., a ceramic sample with an average grain size of 400 nm to 3 μm is obtained. A smaller grain size is conducive to improving the compressive strength of the ceramic sample, thereby improving the energy storage density.
[0053] After testing, the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics described in the present invention has a typical narrow slope hysteresis loop characteristic at room temperature. In some technical solutions, the breakdown electric field of the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics described in the present invention is 444-489 kV / cm; the recoverable energy storage density is 5.55-6.69 J / cm 3 ; The energy storage efficiency is 53.7-76.9%. For example, the lead-free silver niobate-based relaxation energy storage ceramic material of the embodiment has a high saturation polarization (saturation polarization intensity can reach about 50 μC / cm 2 ), low remanent polarization (remanent polarization intensity can be less than 4μC / cm 2 ), high compressive strength (breakdown field strength can reach 489kV / cm) and other characteristics.
[0054] Therefore, the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics of the present invention can be prepared by a solid phase reaction method, which has a simple preparation process and can achieve a breakdown field strength of 489 kV / cm and a breakdown field strength of 6.69 J / cm 3 The energy storage density and energy storage efficiency of 76.9% are achieved.
[0055] Also disclosed herein is a silver niobate-based relaxor energy storage ceramic element, which is made using the above-mentioned silver niobate-based relaxor energy storage ceramic material. In one example, the ceramic material is processed into the required size, cleaned (e.g., ultrasonically cleaned), dried, silvered, and silver-sintered to obtain a silver niobate-based relaxor energy storage ceramic element. The silver-sintering condition can be to keep warm at 650°C for 30 minutes. The temperature can be raised to 650°C at a heating rate of no more than 2°C / minute.
[0056] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0057] Example 1
[0058] The chemical formula of silver niobate-based relaxation energy storage ceramic material for energy storage is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, where x=0.18.
[0059] The solid phase sintering method is used to prepare silver niobate-based relaxation energy storage ceramic materials for energy storage. The specific steps are as follows: (1) According to the chemical formula (1-x) (0.7AgNbO3-0.3NaNbO3)-x (Sr 0.7 Bi 0.2 )TiO3 (x=0.18) is used for mixing. The raw materials are: sodium carbonate with a purity of 99.8%, niobium pentoxide with a purity of 99.99%, silver oxide with a purity of 99.7%, bismuth oxide with a purity of 99.999%, titanium dioxide with a purity of 99.9%, and strontium carbonate with a purity of 99.99%. An electronic balance is used for weighing, and the weighing accuracy is 0.001g.
[0060] (2) The weighed raw materials were mixed and placed in a nylon jar, anhydrous ethanol was added to the jar, zirconium oxide balls were used as ball milling media, and the nylon jar was placed on a planetary ball mill for mixing for 4 hours. Zirconia balls include two different sizes: 6 mm in diameter and 10 mm in diameter. The mass ratio of 6 mm in diameter and 10 mm in diameter is 3:2. The mass ratio of raw material powder: ball milling media: anhydrous ethanol is 1:4.5:1.8. After ball milling, the mixture was poured out and dried in a baking oven, and then sieved with a 40-mesh nylon sieve. The sieved mixed powder was pressed into a cylindrical block with a size of 60 mm in diameter and 20 mm in height on a press. The cylindrical block was synthesized at 870°C for 4 hours in an oxygen atmosphere, and then crushed and sieved through a 40-mesh sieve to obtain a synthetic powder.
[0061] (3) The obtained powder is put into the nylon jar again, and anhydrous ethanol is added to the jar to a level not higher than 2 / 3 of the jar height, and zirconia columns and zirconia balls of different sizes are used as ball milling media. The size of the zirconia column is 7.5 mm in diameter × 7.5 mm in height, and the diameters of the zirconia balls are 6 mm and 10 mm. The mass ratio of zirconia column: zirconia ball with a diameter of 6 mm: zirconia ball with a diameter of 10 mm is 1:1.5:1. The mass ratio of synthetic powder: ball milling medium: anhydrous ethanol is 1:4.5:1. The nylon jar is placed on a planetary ball mill and mixed for 6 hours, then poured out and dried in an oven, and then sieved with a 40-mesh nylon sieve to obtain finely ground powder.
[0062] (4) Add a 7wt% polyvinyl alcohol aqueous solution to the finely ground powder, the amount of which is 6% of the mass of the synthesized powder, and then granulate evenly, pass through a 40-mesh sieve, and press mold to obtain a small cylinder with a size of 13mm in diameter and 1mm in height, and then perform plastic molding. The plastic molding conditions are to heat the mixture to 700°C at a heating rate of no more than 2°C / min in an oxygen atmosphere, keep the temperature for 2 hours, and then cool it to room temperature in the furnace.
[0063] (5) The molded body was sintered in an oxygen atmosphere at a sintering temperature of 1010°C for 2 hours. The sample was taken out after naturally cooling to room temperature.
[0064] The sintered ceramic sample is processed, cleaned, dried and electroded to obtain a ceramic element.
[0065] The prepared silver niobate-based relaxation energy storage ceramic material was tested by X-ray diffraction. Figure 1 The X-ray diffraction pattern of Example 1 is shown. It can be seen that the ceramic of Example 1 is a pure phase.
[0066] The surface of the prepared ceramics was observed. Figure 2 The surface SEM image of Example 1 is shown. It can be seen that the ceramic is sintered densely and the grain size is small, 1 to 1.5 μm.
[0067] The prepared ceramic element was subjected to a unipolar hysteresis loop test at room temperature and 10 Hz. The field strength corresponding to the rightmost end of the hysteresis loop is the breakdown field strength. According to the formula The effective energy storage density is obtained according to the formula The energy storage efficiency is obtained. It can be seen that the hysteresis loop is narrow and the energy storage density is 5.55 J / cm 3 , the energy storage efficiency is 53.7%, the results are attached Fig. 9 .
[0068] Example 2
[0069] The chemical formula of silver niobate-based relaxation energy storage ceramic material for energy storage is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, wherein x=0.2. Except for x=0.2, the other steps are the same as those in Example 1.
[0070] The prepared silver niobate-based relaxation energy storage ceramic material was tested by X-ray diffraction. Figure 1 The X-ray diffraction pattern of Example 2 is shown. It can be seen that the ceramic of Example 2 is a pure phase.
[0071] The surface of the prepared ceramics was observed. Figure 3 The surface SEM image of Example 2 is shown. It can be seen that the ceramic is sintered densely and the grain size is small, 1 to 1.5 μm.
[0072] The dielectric properties were tested using a dielectric impedance spectrometer. The results are attached. Figure 7 Attached Figure 7 The change of dielectric constant with temperature is shown, and it can be seen that the temperature stability of the electrical performance of Example 2 is good.
[0073] The prepared ceramic element was subjected to a unipolar hysteresis loop test at room temperature and 10 Hz. It can be seen that the hysteresis loop is narrow and the energy storage density is 6.54 J / cm 3 , the energy storage efficiency is 69.3%, the results are attached Fig.10 .
[0074] Example 3
[0075] The chemical formula of silver niobate-based relaxation energy storage ceramic material for energy storage is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, wherein x=0.22. Except that x=0.22 and the sintering temperature is 1000°C, the other steps are the same as those of Example 1.
[0076] The prepared silver niobate-based relaxation energy storage ceramic material was tested by X-ray diffraction. Figure 1 The X-ray diffraction pattern of Example 3 is shown. It can be seen that the ceramic of Example 3 is a pure phase.
[0077] The surface of the prepared ceramics was observed. Figure 4 The surface SEM image of Example 3 is shown. It can be seen that the ceramic is sintered densely and the grain size is small, 0.5-1 μm.
[0078] The prepared ceramic element was subjected to a unipolar hysteresis loop test at room temperature and 10 Hz. It can be seen that the hysteresis loop is narrow and the energy storage density is 6.69 J / cm 3 , the energy storage efficiency is 76.9%, the results are attached Fig.11 .
[0079] Example 4
[0080] The chemical formula of silver niobate-based relaxation energy storage ceramic material for energy storage is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, wherein x=0.25. Except that x=0.25 and the sintering temperature is 1000°C, the other steps are the same as those of Example 1.
[0081] The prepared silver niobate-based relaxation energy storage ceramic material was tested by X-ray diffraction. Figure 1 The X-ray diffraction pattern of Example 4 is shown. It can be seen that the ceramic of Example 4 is a pure phase.
[0082] The prepared ceramic element was tested for unipolar hysteresis loop at room temperature and 10 Hz. It can be seen that the hysteresis loop is narrow and the energy storage density is 6.11 J / cm 3 , the energy storage efficiency is 74.2%, the results are attached Fig.12 .
[0083] Comparative Example 1
[0084] The ceramic material composition in Comparative Example 1 is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, wherein x=0. Except for x=0, the other steps are the same as those in Example 1.
[0085] The prepared ceramic material was tested by X-ray diffraction. Figure 1 The X-ray diffraction pattern of Comparative Example 1 is shown. It can be seen that the ceramic of Comparative Example 1 is a pure phase.
[0086] The surface of the prepared ceramics was observed. Figure 5The surface SEM image of Comparative Example 1 is shown. It can be seen that the ceramic is sintered densely and the grain size is large, 2 to 3 μm.
[0087] The prepared ceramic element was subjected to a unipolar hysteresis loop test at room temperature and 10 Hz. It can be seen that the energy storage density is 1.15 J / cm 3 , the energy storage efficiency is 21.9%, the results are attached Fig.13 .
[0088] Comparative Example 2
[0089] The ceramic material composition in Comparative Example 2 is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, wherein x=0.1. Except for x=0.1, the other steps are the same as those in Example 1.
[0090] The prepared ceramic material was tested by X-ray diffraction. Figure 1 The X-ray diffraction pattern of Comparative Example 2 is shown. It can be seen that the ceramic of Comparative Example 2 is a pure phase.
[0091] The surface of the prepared ceramics was observed. Figure 6 The surface SEM image of Comparative Example 2 is shown. It can be seen that the ceramic is sintered densely and the grain size is large, 1.5 to 2 μm.
[0092] The prepared ceramic element was subjected to a unipolar hysteresis loop test at room temperature and 10 Hz. It can be seen that the hysteresis loop is straight and the energy storage density is 3.51 J / cm 3 , the energy storage efficiency is 45.1%, the results are attached Fig.14 .
[0093] Comparative Example 3
[0094] The ceramic material composition in Comparative Example 3 is (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, wherein x=0.15. Except for x=0.15, the other steps are the same as those in Example 1.
[0095] The prepared ceramic material was tested by X-ray diffraction. Figure 1 The X-ray diffraction pattern of Comparative Example 3 is shown. It can be seen that the ceramic of Comparative Example 3 is a pure phase.
[0096] The dielectric properties were tested using a dielectric impedance spectrometer. The results are attached. Figure 8 Attached Figure 8 is the change of dielectric constant with temperature, and it can be seen that the material is in the antiferroelectric M2 phase.
[0097] The prepared ceramic element was tested for unipolar hysteresis loop at room temperature and 10 Hz. It can be seen that the hysteresis loop is straight and the energy storage density is 4.64 J / cm 3 , the energy storage efficiency is 48.9%, the results are attached Fig.15 .
[0098] Attached Fig.16 It is the change of energy storage density and energy storage efficiency with x. It can be seen that when x = 0.2, the energy storage density and energy storage efficiency are significantly improved, and when x = 0.25, the energy storage performance is slightly reduced compared with x = 0.22. (Sr 0.7 Bi 0.2 )TiO3 significantly improves the energy storage performance.
[0099] Table 1 shows the composition and performance parameters of the silver niobate-based ceramics prepared by the present invention:
[0100]
[0101] from Figures 1 to 16 As can be seen from Table 1, with (Sr 0.7 Bi 0.2 ) TiO3 content increases. Although all ceramic materials are pure phase, the hysteresis loops of Examples 1 to 4 are narrower and more inclined than those of Comparative Examples 1 to 3, and the energy storage density ranges from 1.15 to 4.64 J / cm 3 Increased to 5.55~6.69J / cm 3 , the energy storage efficiency increased from 21.9~48.9% to 53.7~76.9%, (Sr 0.7 Bi 0.2 )TiO3 significantly improves the energy storage performance of ceramics, and the appropriate amount of (Sr 0.7 Bi 0.2 )TiO3 is introduced to obtain high energy storage performance.
Claims
1. A silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage properties, characterized in that: The chemical composition of the silver niobate-based relaxation-type ternary solid solution ceramic material with high energy storage properties is: (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, where 0.18 ≤ x ≤ 0.
25.
2. The silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics according to claim 1, characterized in that: The breakdown electric field of the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics is 444-489 kV / cm; the recoverable energy storage density is 5.55-6.69 J / cm 3 ; The energy storage efficiency is 53.7~76.9%.
3. A method for preparing the silver niobate-based relaxor-type ternary solid solution ceramic material with high energy storage characteristics according to claim 1 or 2, characterized in that: The preparation method comprises: (1) According to the stoichiometric ratio (1-x)(0.7AgNbO3-0.3NaNbO3)-x(Sr 0.7 Bi 0.2 )TiO3, weighing silver oxide powder, niobium pentoxide powder, titanium dioxide powder, sodium carbonate powder, bismuth oxide powder and strontium titanate powder as raw material powders, mixing them, calcining and fine grinding them to obtain synthetic powder; (2) mixing the obtained synthetic powder and a binder, and then granulating, aging, sieving and molding to obtain a ceramic green body; (3) The obtained ceramic green body is subjected to plastic disassembly and sintering to obtain a silver niobate-based relaxation-type ternary solid solution ceramic material with high energy storage properties.
4. The preparation method according to claim 3, characterized in that: In step (1), the mixing method is ball milling.
5. The preparation method according to claim 4, characterized in that: Anhydrous ethanol is used as the dispersion medium, the ball milling speed is 230-250 rpm, and the ball milling time is 4-6 hours.
6. The preparation method according to claim 4, characterized in that: The ball milling media are zirconia balls and / or zirconia columns.
7. The preparation method according to claim 3, characterized in that: In step (1), the calcination atmosphere is an oxygen atmosphere, the calcination temperature is 850-870° C., and the calcination time is 2-4 hours.
8. The preparation method according to claim 3, characterized in that: In step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 5 to 7 wt%; the amount of the binder added is 6 to 7 wt% of the mass of the synthetic powder; and the sieve is 20 to 80 meshes.
9. The preparation method according to claim 3, characterized in that: In step (3), the temperature of the plastic removal is 700-800°C and the time is 2-3 hours.
10. The preparation method according to claim 3, characterized in that: In step (3), the sintering temperature is 980°C to 1060°C, and the time is 2 to 3 hours; the sintering heating rate is not higher than 2°C / min.
Citation Information
Patent Citations
Lead-free anti-ferroelectric ceramic material with high energy storage density and preparation method of lead-free anti-ferroelectric ceramic material
CN114804870A
Superparaelectric phase sodium bismuth titanate-based relaxation energy storage ceramic material and preparation method thereof
CN116693285A